2013
DOI: 10.1016/j.imlet.2013.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Cell mediated innate responses of cattle and swine are diverse during foot-and-mouth disease virus (FMDV) infection: A unique landscape of innate immunity

Abstract: Pathogens in general and pathogenic viruses in particular have evolved a myriad of mechanisms to escape the immune response of mammalian species. Viruses that cause acute disease tend to bear characteristics that make them very contagious, as survival does not derive from chronicity of infection, but spread of disease throughout the herd. Foot-and-mouth disease virus (FMDV) is one of the most contagious viruses known. Upon infection of susceptible species, cloven-hoofed animals, the virus proliferates rapidly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 109 publications
0
36
0
Order By: Relevance
“…2 FMDV induces a variety of host innate immune responses, which likely contributes to viral pathogenesis and/or influence the final outcome of viral infection in vitro and in vivo. 3 The innate immune response of the host is the first line of defense against viral infection until specific protection is established by the adaptive immune system. However, FMDV has evolved to counteract the host innate immune response.…”
Section: Introductionmentioning
confidence: 99%
“…2 FMDV induces a variety of host innate immune responses, which likely contributes to viral pathogenesis and/or influence the final outcome of viral infection in vitro and in vivo. 3 The innate immune response of the host is the first line of defense against viral infection until specific protection is established by the adaptive immune system. However, FMDV has evolved to counteract the host innate immune response.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that FMDV interacts with DCs both in mice and in natural host [27,28]. However, the mechanisms involved in this interaction, are not well known.…”
Section: Discussionmentioning
confidence: 99%
“…Bovine NK cells, like those of other species, have CD335 (natural cytotoxicity receptors), exhibit production of IFN‐γ, lyses of sensitive targets, and appear to have CD335 + /CD2 +/− /CD8 +/− /CD3 − phenotype. It has been shown that the NK cells isolated from cattle, infected with FMDV, have a high cytotoxicity level against the cells of bovine origin in vitro …”
Section: Introductionmentioning
confidence: 99%
“…Dendritic cells are responsible for scanning for antigens (including vaccine antigen) in the margins and directing them to the regions of lymph nodes concentrated with T cells to initiate immune responses. The maturation of APCs results in uptake of amplified antigen and presentation of viral peptides via MHC classes I and II molecules . These antigenic peptides on the surface of macrophages lead to the stimulation and maintenance of T cell response against FMD virus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation